Addressing Climate Challenges in ECA Cities - World Bank (World Bank, Washington, DC, 2016)
Much of the world’s built environment is found in urban areas, and cities are thought to be responsible for up to 70 percent of global greenhouse gas (GHG) emissions, and up to 80 percent of primary energy demand. Most of the energy consumed in the world fuels urban industry, powers urban homes and offices, and moves people within and between cities. This paper is about climate change mitigation in cities, and will primarily look at how local authorities can provide a higher quality of life for their citizens while at the same time achieving higher resource efficiency. It will also look at how climate change mitigation measures could help boost local employment and drive economic growth. The focus will be on buildings (residential, commercial, and office), public services infrastructure (water, sewage, solid waste management, and public lighting), and urban form. Other topics of interest in this respect, such as transport and industrial production will be discussed tangentially in relation to the other topics (e.g. urban form influences and is influenced by transport patterns and strategies).